Metode Kritik Ulama Terdahulu di dalam Buku Manhaj an-Naqdi ‘inda al-Muhaditsin Nasy’atuhu wa Tarikhuhu - Hilabi, Muhamad Fikri (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2023)
Orientalists claim that the previous scholars did not have a method in hadith criticism, and this resulted in some of them choosing the hadiths of the Prophet sallallahu 'alayhi wa sallam. The purpose of this study is to explain that previous scholars have a method in criticizing hasis. And the method used in this research is qualitative with the analytical approach in the book. The conclusion of this study is that the previous ulum has three methods of hadith criticism that have existed since the time of the Prophet, and continued to develop until the time after the Companions, and the scholars were very strict in nature.